The Effect of Online Teaching and Learning Activities During the Covid-19 Pandemic on Stress Among Students of The Faculty of Medicine Ciputra University - I Made Irham Muhammad; imelda ritunga; Azimatul Karimah; Hebert Adrianto (Faculty of Medicine, Public Health, and Nursing, 2022)
Background: The World Health Organization has declared that COVID-19 is a global pandemic. To prevent its spread, academic activities in Indonesia have been shifted to distance learning methods. This change resulted in students having to adapt to these new methods and deal with the additional stress. The inability of students to adapt contributed to the new conditions causing the additional stress. Objectives: This study aimed to analyze the effect of online teaching and learning activities during the COVID-19 pandemic on stress at the Faculty of Medicine, Ciputra University, Surabaya Indonesia. Methods: The quantitative method used was in the form of analytical observations with a cross-sectional approach. The respondents consisted of 63 people, selected using simple random sampling. Data analysis used linear regression tests to determine the effect of the second variable. Results: The results showed that there was no significant effect (p= 0.052) between Online Teaching and Learning Activities During the COVID-19 Pandemic Period on Stress in the Medical Faculty Students, Ciputra University, Surabaya, Indonesia. Students have started to become accustomed to the strategies to deal with the additional stress and its effects. Other supporting factors in the implementation of online learning are flexibility, time efficiency, low learning costs, and learning materials which can be accessed at any time with technological applications, using simple storage of learning materials. Conclusions: There was no significant influence found from the online learning on student stress.